Examining the effects of multiple chronic conditions on cognitive decline and potential moderators among older Koreans: Findings from the Korean Longitudinal Study of Ageing 2006–2016. (July 2021) - Lee, Yura; Cho, Chi C.
Highlights: The presence of multiple chronic conditions is related with cognitive decline among older Koreans Risk factors contributing to cognitive decline differ across groups with different number of chronic conditions. Self-management programs that target each group may help mitigate cognitive decline in this population Abstract: Background: More than half of older Koreans have two or more chronic conditions, known as multiple chronic conditions (MCC). Successful self-management (e.g., diet control, exercise, taking medications) is critical to prevent worsening of condition or acquisition of additional chronic conditions. This study investigated the effects of MCC on cognitive decline and risk factors in each chronic condition group over a 10-year period. Methods: Six waves (2006–2016) of the Korean Longitudinal Study of Ageing were used, featuring 2, 198 older adults who were cognitively healthy at baseline. MCC were categorized into three groups: no chronic condition ( n =831), one chronic condition ( n =813), and two or more chronic conditions ( n =554). Linear mixed-effects model analyses were conducted using SAS 9.4. Results: Individuals with MCC showed greater cognitive decline than those with no or one chronic condition. Different factors were associated with cognition in each group. Among those with no chronic condition, age, income, education, and functional limitation were associated with cognitive decline. Among those with one chronic condition, age, marital status, working status, self-rated health, and arthritis were associated with cognitive decline. Among those with two or more chronic conditions, age, income, marital status, and living arrangement were associated with cognitive decline. Listed factors have p-values less than .05. Conclusions: Findings indicate MCC is significantly related with cognitive decline. Risk factors for cognitive decline differed across three chronic condition groups. Self-management programs that target each group can be a promising strategy to mitigate cognitive decline among older Koreans.